2013
DOI: 10.1108/09654281311309855
|View full text |Cite
|
Sign up to set email alerts
|

Project Health: evaluation of a project‐based health education program

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
(96 reference statements)
4
6
0
Order By: Relevance
“…Economically disadvantaged students at Beta, the campus utilizing a PjBL saturated environment, attended school at higher rates than students at Alpha, utilizing a traditional instructional approach. These findings are consistent with the effects of PjBL and PBL on attendance rates in various environments studied in previous research conducted on entire student populations (Smith & Cook, 2012;Zusevics, Lemke, Harley, & Florsheim, 2013).…”
Section: -2012 School Yearsupporting
confidence: 92%
See 1 more Smart Citation
“…Economically disadvantaged students at Beta, the campus utilizing a PjBL saturated environment, attended school at higher rates than students at Alpha, utilizing a traditional instructional approach. These findings are consistent with the effects of PjBL and PBL on attendance rates in various environments studied in previous research conducted on entire student populations (Smith & Cook, 2012;Zusevics, Lemke, Harley, & Florsheim, 2013).…”
Section: -2012 School Yearsupporting
confidence: 92%
“…Although implementing a PjBL environment requires ongoing training and support for teachers to be able to integrate PjBL methodologies within complex educational content required by state and national standards, PjBL may increase student interest and engagement in school. Because PjBL, as well as PBL, appear to affect the attendance rates of students, as evidenced by the results of this study and others (Smith & Cook, 2012;Zusevics et al, 2013), an effective implementation of PjBL methodology may lead to more of our economically disadvantaged students attending school on a more regular basis and actively striving toward graduation. Additionally, increased rates of attendance by economically disadvantaged students may impact not only graduation rates, but also accountability ratings for the study school and district.…”
Section: Discussionsupporting
confidence: 51%
“…These findings are consistent with the effects of PBL on selfefficacy in various environments studied in previous research conducted on entire student populations (Zusevics, Lemke, Harley, & Florsheim, 2013).…”
Section: Problem Solvingsupporting
confidence: 92%
“…Previous studies have shown that PBL methodologies may positively impact student attitudes, collaboration, and buy-in, and these factors may contribute to the higher self-efficacy rates as shown in the study (Zusevics, Lemke, Harley & Florsheim 2013). In this light, we might consider the founding principles of PBL methodology in providing relevant, learner-centered experiences for all students.…”
Section: Adriana the Foreman In The Makingmentioning
confidence: 75%
“…Although students could learn about genomics in traditional learning techniques (ie, textbook reading, teacher lecture), this field is likely to be one best taught through the use of technology and nontraditional teaching modalities (such as using Apps on mobile devices and tablets or computer‐based software games) integrated into an existing health education program. As previous studies have shown, technology‐based health education has the potential to improve academic outcomes and decrease absenteeism . Using technology to integrate genomic content into health education curricula may engage students more as they learn about personal and community health, potentially leading to improved educational outcomes.…”
mentioning
confidence: 99%